KEGIATAN INESIAN MEMBENTUK KARAKTER RELIGIUS ANAK USIA 3-4 TAHUN DI KB KATOLIK SANTA CLARA SURABAYA BERDASARKAN TEORI THOMAS LICKONA - Anneke, Christabel; Takumansang, Regina Christine (Lembaga Penelitian STKIP Widya Yuwana, 2025)
This study observes how Inesian educative activities form the religious character of children aged 3-4 years. The Inesian educative approach emphasizes nurturing the Catholic faith and values of Beata Maria Ines Teresa Arias in children. Inesian activities are unique because they focus on different values from the values taught in other Catholic schools in Surabaya. The study takes a qualitative approach to observe the case study of Santa Clara Catholic Kindergarten in Surabaya. The data sources for this study are the observation of B2 Kindergarten children and interviews with Inesian activity teachers which were collected in the 7 days of study period. The Miles & Huberman model was used to analyze the data in this study. The results of this study show that Inesian activities can form the religious and daily character of the observed children by reinforcing consistent habits in school.